Communication policies of Spanish universities targeting prospective students: an evaluation by secondary schools (Avaliação: Revista da Avaliação da Educação Superior, 2016)
This paper presents an evaluation of the communication policies through which Spanish universities help to facilitate young people’s passage from secondary to higher education. The underlying data have been gathered through a survey conducted with guidance providers at a sample of Spanish secondary schools, as well as through a series of in-depth interviews involving these same teachers. The research has led to the conclusion that the career guidance tendered by secondary schools is provided within a setting of relative precariousness in terms of information: the teachers surveyed consider that the importance of the briefing content they receive always exceeds the quality of the manner in which this information is forthcoming. The developments in the design of new university qualifications and the criteria applied by Spain’s National Agency for Quality Assessment and Accreditation (ANECA) constitute a magnificent opportunity for improvement in this field.